2019
DOI: 10.1021/acs.cgd.9b00154
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Polymorphism of Carbamazepine Nanoparticles in a Continuous Supercritical-CO2-Assisted Spray Drying Process

Abstract: Controlling polymorphism in the transition from batch to continuous crystallization represents a major obstacle for the pharmaceutical industry. This work demonstrates a novel methodology to control the polymorphism of carbamazepine (CBZ) nanoparticles, a highly polymorphic BCS class II drug, using a continuous supercritical CO 2 antisolvent-assisted nano spray drying (SASD) process. We show herein that when supersaturation conditions are achieved in the highpressure SASD nozzle in the presence of anionic addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 67 publications
0
14
0
Order By: Relevance
“…This step is similar to the semi-continuous SAS process, and it is possible to control the solid-state properties of APIs by controlling the supersaturation/nucleation events. In general, the ratio of SCF to solution is considerably high in the continuous process when compared to the values obtained in the batch or semi-continuous SAS experiments, strongly ensuring that anti-solvent nucleation are occurring in the nozzle [ 75 ]. The generated nano-suspension is then spray-dried after the nozzle orifice.…”
Section: Discussion Of the Manipulation Of The Solid-state Properties Of Apismentioning
confidence: 99%
See 2 more Smart Citations
“…This step is similar to the semi-continuous SAS process, and it is possible to control the solid-state properties of APIs by controlling the supersaturation/nucleation events. In general, the ratio of SCF to solution is considerably high in the continuous process when compared to the values obtained in the batch or semi-continuous SAS experiments, strongly ensuring that anti-solvent nucleation are occurring in the nozzle [ 75 ]. The generated nano-suspension is then spray-dried after the nozzle orifice.…”
Section: Discussion Of the Manipulation Of The Solid-state Properties Of Apismentioning
confidence: 99%
“…In fact, the study of Long et al [75] have demonstrated that the polymorphic outcome of carbamazepine (CBZ) were controllable by using different additives in a continuous SAS process: (1) when using ethyl cellulose as an additive, amorphous CBZ was obtained;…”
Section: Discussion Of the Manipulation Of The Solid-state Properties Of Apismentioning
confidence: 99%
See 1 more Smart Citation
“…Such qualitative conclusions are confirmed by Rietveld refinement, according to which the relative amount of each phase coincides with that of the starting materials (Table S1). On the contrary, the same technique indicates that a single microcrystalline phase is obtained when CO 2 is employed in a supercritical CO 2 assisted spray drying (SASD) process (Long et al, 2019(Long et al, , 2020Padrela et al, 2017) (Fig. 3).…”
Section: Bulk Synthesis and Propertiesmentioning
confidence: 94%
“…Droplet agglomeration is also avoided with the improved and faster mixing promoted in SAS-EM, leading to the formation of droplets and, consequently, smaller particles than those produced by the conventional SAS process. Long et al [103] used the supercritical CO 2 antisolventassisted nano spray-drying (SASD) process to control the polymorphism of carbamazepine nanoparticles; in the SASD process, CO 2 mixes with the solution containing the active principle in a small-volume high-pressure coaxial nozzle, in which supersaturation occurs. In this process, the atomization is involved in the method itself, resulting in the generation of a spray of ultrafine droplets in which the solvent is removed by thermal means.…”
Section: Production Of Nanoparticles By Using Co 2 As An Antisolventmentioning
confidence: 99%